Estimación de la relación entre el estado de conservación de la zona riparia y calidad biológica del agua en la microcuenca Jipiro, cantón Loja - Elizalde Armijos, Paula Alejandra (2024)
The riparian zones of the Jipiro micro-basin are key to the balance of river ecosystems, contributing significantly to the ecological vitality of water courses and the diversity of aquatic organisms. However, these areas are increasingly threatened by the expansion of human and livestock activities. This study aimed to estimate the relationship between the conservation status of the riparian zone of the Jipiro micro-basin and the biological quality of the water, in a gradient of human intervention. Three conservation states were selected; high zone (conserved), medium (partially conserved), and low (intervened). In each zone, a 200 m long section with 10 systematic transects was established. A D-net type net was used to collect macroinvertebrates and their subsequent identification. The riparian vegetation quality protocol (QBR Index) was also implemented. Using CABIRA, five metrics were calculated, including the biological quality indices (ABI and IMEERA) and finally, in Past 4.04, the diversity of macroinvertebrates. In the QBR index, the results for the upper zone are good; for the middle zone, they are acceptable; and for the lower zone, they are of poor quality. This shows that the lower the human activity, the better the state of conservation. Likewise, the upper zone showed greater diversity and a lower quantity of taxa tolerant to pollution. The lower zone presented an intermediate diversity, while the middle zone had the lowest diversity, both with a greater quantity of tolerant taxa. In addition, the Tukey test determined that the upper and middle zones presented significantly different diversities, while the lower zone does not differ from the other two.